Caracterização Geoquímico-Ambiental do Garimpo do Tucano, Monte Alegre de Goiás-GO - TIBIRIÇÁ, Luciana Gonçalves (2006)
The environmental analysis of impacts caused in the Tucano s Garimpo was carried out from the environmental liabilities of artisanal mining and the association of diverse spheres of the knowledge, integrating the physical, biological and social means. The mercury and his unconscious control were considered the research s central factors, guiding the main chemical analyses: hair of the inhabitants of the garimpo, muscles of fish, sediments of the dam and the stacks of mining. However, as the environment of the garimpo is not isolated from the ecosystem, were considered also the elements that compose and the parameters physical-chemical of the waters from the area represented by the dam and mining area. These analyses brought additional facts, enriching an already traditional methodology of monitoring contaminated and degraded areas by the golden mining in this case, by an artisanal mining. The results indicate localities still not contaminated, that should be frequently monitored and others that should be isolated. Still reveals the good condition of human health and of the ictiofauna regarding the mercury, even surrounded by an unhealthy environment instituted by the artisanal mining.